A new species of Stereocyclops Cope (Anura, Microhylidae) from Southeastern Brazil - Caramaschi, Ulisses; de Oliveira Lula Salles, Rodrigo; Cruz, Carlos Alberto Gonçalves (Zootaxa, 2012)
A new species of Stereocyclops is described from the Zona da Mata Regional Airport (21o 31’S, 43o 11’W; 408 m a.s.l.),Municipality of Goianá, State of Minas Gerais, Southeastern Brazil. Stereocyclops palmipes sp. nov. is characterized by itsmedium size (SVL 43.7–48.5 mm in males; SVL 48.4–56.7 mm in females); in males, large, numerous dermal spinesconcentrated in the inferior border of mandible, forming a band; dermal spines scattered on ventral surfaces of body, arms,fingers, legs, toes, and pericloacal region of males, and agglomerate only in pericloacal region and ventral surfaces of thighs infemales; fringes and interdigital membranes of toes developed; color pattern composed by two mid-dorsal, poorly defined, dark brown stripes from the inguinal regions to head, passing on the occipital dermal fold and reaching the upper eyelid.